Comparative study between histochemical mucus volume, histopathological findings, and endocytoscopic scores in patients with ulcerative colitis. Issue 9 (3rd March 2023) - Kamitani, Yu; Kurumi, Hiroki; Kanda, Tsutomu; Ikebuchi, Yuichiro; Yoshida, Akira; Kawaguchi, Koichiro; Yashima, Kazuo; Umekita, Yoshihisa; Isomoto, Hajime
Abstract : Ulcerative colitis (UC) causes a reduction in goblet cells. However, there have been few reports on the relationship between endoscopic and pathological findings and mucus volume. In this study, we quantitatively evaluated histochemical colonic mucus volume by fixing biopsied tissue sections taken from patients with UC in Carnoy's solution and compared it with endoscopic and pathological findings to determine whether there is a correlation between them. Observational study. A single-center, university hospital in Japan. Twenty-seven patients with UC (male/female, 16/11; mean age, 48.4 years; disease median duration, 9 years) were included in the study. The colonic mucosa of the most inflamed area and the surrounding less inflamed area were evaluated separately by local MES and endocytoscopic (EC) classification. Two biopsies were taken from each area; one was fixed with formalin for histopathological evaluation, and the other was fixed with Carnoy's solution for the quantitative evaluation of mucus via histochemical Periodic Acid Schiff and Alcian Blue staining. The relative mucus volume was significantly reduced in the local MES 1–3 groups, with worsening findings in EC-A/B/C and in groups with severe mucosal inflammation, crypt abscess, and severe reduction in goblet cells. The severity of inflammatory findings in UC by EC classification correlated with the relative mucus volume suggesting functional mucosal healing. We found a correlation between the colonic mucus volume and endoscopic and histopathological findings in patients with UC, and a stepwise correlation with disease severity, particularly in EC classification.